Amalgam allergy and Burning Mouth Syndrom: treatment and 25 years recall - De Paiva Gonçalves, Sérgio Eduardo [UNESP]; Silva, Regina Célia Santos Pinto [UNESP]; Gomes, Ana Paula Martins [UNESP]; Yui, Karen Cristina Kazue [UNESP]; Barcellos, Daphne Camara; Bresciani, Eduardo [UNESP]; Özcan, Mutlu (Editora Cubo, 2021)
Background: Burning mouth syndrome (BMS) is a non-neuropathic chronic orofacial pain condition, characterized by the presence of burning/warm sensation without specific mucosal lesions. Objective: The aim of the present clinical case report is to describe the positive outcome of dental treatment of a patient with BMS and followed up for 25 years. Data Treatment: This report describes the case of a 50-year-old black woman sought treatment for burning, and persistent swelling of tong (24h/day) occurring over years. Clinical evaluation of the oral environment revealed the tongue with cracking, darkened points areas, surrounded by whitish areas. Twelve teeth presented extensive amalgam restorations. Patch testing revealed a very strong hypersensitivity to Amalgam. All amalgam restorations were substituted by composite resin restorations. Results and Conclusion: Burning sensation disappeared completely after these restorations had been changed. After 25-year follow-up period, it was observed that burning sensation has never been felt anymore. Clinical Signi icance: Burning mouth syndrome is a chronic orofacial pain, usually without specific mucosal lesions. The etiology is complex and multifactorial and the treatment should be made specifically for each pacient.
Keywords: Burning mouth syndrome; Composite resin; Dental amalgam